Entry of Foreign Investments: Convergence of International Trade and Investment Law? - Lubambo de Melo, Murilo Otávio (University College London, 2018)
The thesis analyses how public international law regulates the entry of foreign investors and investments into states. It explores the various legal concepts and techniques to limit the freedom of states to accept investments and regulate their access, employed in different regimes of international law. These are: international trade law – mainly illustrated by the WTO (World Trade Organisation) agreements, in particular, the General Agreement on Trade in Services (GATS), and preferential trade agreements (PTAs) – and international investment law (IIL) – scattered through a network of bilateral investment treaties (BITs). The thesis concludes that there are signs that the international rules regulating the entry of investments in services are converging in several levels of alignment and treaty making. Convergence means a reduction of non-shared legal and systemic characteristics or an increase in shared characteristics. Several factors support this conclusion: the progressive incorporation in treaties of establishment rights for investors, that is, commitments by states to allow foreign investments under certain conditions; the narrowing-down of investor-state dispute settlement clauses dealing with entry, which makes IIL systemically closer to international trade law regarding dispute settlement; the hidden liberalising power that flows from the broad interaction of the most-favoured-nation (MFN) clauses in the GATS and IIL with entry provisions; and, the incorporation of concepts and techniques from the international trade law world into investment chapters of larger international economic agreements, such as the GATS absolute standard of market access and its system of exceptions and justifications. These converging signs are considered a natural evolution of the rules given that trade and investment sometimes represent complementary market access strategies in the context of global value chains. The thesis suggests that this move towards convergence may bring about more effectiveness to the rules by attaining the goal of investment liberalisation balanced with the safeguard of regulatory space.
Keywords: Domestic investor; Foreign investment; GATS MFN clause; International Economic Law; International Trade; Investment Law; Investments; Remedies; State-State Investment Arbitration; WTO regulation

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

A critical analysis of the legal environment in respect of the private equity industry in South Africa - Oaker, Wentzel (Stellenbosch University, 2018)
This dissertation aims to answer a fundamental question relating to the South African legal and economic framework in which private equity operates. This being: To what extent does the law address/regulate the structure of private equity funds and the relationships between the various parties related to a fund, that is: investors, the fund manager and underlying portfolio investments? This thesis also discussed how the law could better regulate the private equity industry. The dissertation consists of five chapters. Chapter one raises such fundamental questions as ‘what is the nature of private equity?’ by looking at the parties involved, the private equity cycle, returns, liquidity, the risk, and the private equity market. In addition, it assesses whether private equity satisfies the criteria to be regarded as a separate asset class. Chapter two provides an analysis of the key features of private equity fund formation in South Africa. The choice of the most appropriate legal structure of a private equity fund starts with the choice of the most effective and suitable legal vehicle. Chapter two includes a discussion of the general private equity fund structure, the regulatory requirements of private equity firms, and certain regulatory considerations relevant in operating a private equity fund in South Africa. The discussion at certain instances reference private equity fund formation in foreign jurisdictions such the US, UK, Australia, and Canada. Chapter three introduces an analysis of corporate governance as it pertains to private equity funds. Firstly, it discusses the role of corporate governance regulation in stimulating investment. Secondly, it discusses the importance and benefits of corporate governance from the perspective of private equity managers; and seeks to explain the link between the private equity business model and corporate governance that is based on the assertion that there are two levels of corporate governance involved in private equity investing. The first level of governance relates to the private equity fund’s underlying portfolio investee companies and this includes inter alia, a discussion on the duties of the fund manager, particularly in their capacity as serving as directors on the boards of such companies. The second level of governance relates to the private equity fund itself which focuses on the relationship between the private equity firm and the investors that invest in the private equity fund. Chapter four examines two key impediments namely tax legislation and exit alternatives; and show how legislation could effectively address the former and how the lack of exit routes is an impediment to the growth of the local private equity industry. Chapter five states that, the development of the above mentioned regulatory framework will only be successful if the private equity industry participants themselves acknowledge and actively address the disadvantages and real risks posed by the private equity industry on the South African financial system.
Keywords: Investments; Private equity; Private equity funds; South Africa; Taxation

Factors Influencing Indian Firms Decision Making In Foreign Direct Investment In Africa - Kukreja, Mukta; Joshi, Mahesh Chandra (International Journal of Applied Business and International Management, 2018)
India's economic progress and relations with other developing regions have received much attention, particularly the way in which Indo-African relations have evolved since 2000. This paper aims to put Indian FDI in Africa into perspective and provide some answers on the nature and possible impact of these flows to the continent. The study utilized the International typology offered by Dunning OLI paradigm to identify the important of Location Specific Advantages and how these advantages leads to selection of location for investment purposes by investors The study findings demonstrated that potential market growth, market opportunities and consumer base are the important indicated Indian firms targets Africa to seek new and unexplored markets of Africa. Competitiveness climate is important determinant along with economies of scale, investment incentives and availability of natural resources.
Keywords: African nations; Developing countries; FDI; India; Indo-Afro relations; Investments; Multinational companies; OLI eclectic paradigm

Shareholders' claims for reflective loss in international investment arbitration - the rule and its demystification - Vanhonnaeker, Lukas (McGill University, 2018)
In recent years, investor-State tribunals have often permitted shareholders' claims for reflective loss despite the well-established principle of no reflective loss applied consistently in domestic regimes and in other fields of international law. Investment tribunals have justified their decisions by relying on definitions of "investment" in investment agreements that often include "shares", while the no-reflective-loss principle is generally justified on the basis of policy considerations pertaining to the preservation of the efficiency of the adjudicatory process and to the protection of other stakeholders, such as creditors. Although these policy considerations militating for the prohibition of shareholders' claims for reflective loss also apply in investor-State arbitration, they are curable in that context and must be balanced with policy considerations specific to the field of international investment law that weigh in favor of such claims: the protection of foreign investors in order to promote trade and investment liberalization.
Keywords: Arbitrage; Arbitragem; Arbitration; International Arbitration; International Investment Arbitration; Investments; Reflective loss; Shareholder claims